Dermatofunctional physiotherapy treatment in abdominal lipodystrophy: review (Research, Society and Development, 2023)
Localized lipodystrophy corresponds to the accumulation of fat in specific regions of the body, not related to obesity. There are several dermatofunctional physiotherapy treatments for localized lipodystrophy. The aim of this study was to carry out a review of the most current literature on dermatofunctional physiotherapy treatments for lipodystrophy located in the abdominal region. A literature review was carried out by selecting articles in the Bireme, Lilacs, Scielo and Google Scholar databases, in Portuguese, between 2020 and 2023, through the intersection of the words “localized fat”, “localized lipodystrophy”, or “localized adiposity”, with the expression “dermatofunctional physiotherapy”. Among the 284 articles found, 10 were selected, according to the inclusion and exclusion criteria. The works found addressed the electrotherapeutic resources frequently used in the treatment of localized lipodystrophy, such as: radiofrequency, electrolipolysis, cryolipolysis, carboxytherapy, excitomotor current, ultrasound, among others. It was concluded that there are several current treatments in the area of dermatofunctional physiotherapy, all with positive effects on lipodystrophy, enhanced when associated with each other. The association with a guided diet, change of life habits and practice of physical exercises is essential for faster and more effective results.